Retroceso glacial reciente en el Campo de Hielo Norte, región de Aysén, Chile: relación con variaciones climáticas. - Mardones F., María; Aguayo A, Mauricio .; Smith A., Ernesto; Ruiz L., Paulina (Revista de Geografía Norte Grande, 2018)
We study the fluctuations seven North Ice Field glaciers and their relationship with decadal climatic variations post Little Ice Age, through bibliography, interpretation of cartographic documents, aerial photographs, satellite images and terrain surveys. Decadal climatic variations are obtained from the records of Puerto Aysén and Balmaceda meteorological stations. Widespread, continuous and synchronous glacial regression on both slopes of the icefield is observed, disturbed only by small advances in the 1920s and 1940s. Since 1972 precipitation has declined and temperatures have increased; simultaneously the rate of glacial retreat accelerates, culminating with a collapse of much of the glacial fronts in the 1990s. The geomorphological eff ects of the glacial retreat is setting a new proglacial geomorphology and danger zones associated with paraglacial processes.